Historiosophy and Zev Garber, a Neologism: His Teaching Methodology, Literary Investigations, and Engagement with Zionism - Sabbath, Roberta (Hebrew studies, 2010)
Zev Garber’s signature mantra, historiosophy, demonstrates his commitment to using sacred text to shine a light on the moral issues of contemporary life, in general, and the life of the Jewish people, in particular. Garber’s existential voice calls for the celebration of life, the power of faith, and the importance of moral action in the midst of confusion and evil, insisting that these are the secrets for survival. His teaching, his aesthetics, his epistemology, and his politics form a holistic approach to life, learning, and beauty. This essay explores, using a figural structure, the dimensions of Garber’s voice—suggesting PaRDes.